Movement patterns and space use of the first giant anteater (Myrmecophaga tridactyla) monitored in São Paulo State, Brazil. (2nd January 2017) - Bertassoni, Alessandra; Mourão, Guilherme; Ribeiro, Rullian César; Cesário, Clarice Silva; Oliveira, Juliana Paula de; Bianchi, Rita de Cassia
ABSTRACT: This study analyzes a giant anteater's ( Myrmecophaga tridactyla ) movement patterns and space use in São Paulo, Brazil. It is the first study to track a giant anteater with Iridium-GPS. The anteater traveled an average distance of 1326 m day –1 with an average speed of 1.04 m min –1 . Home range by Kernel was 2.46 km 2 while the core area was 0.75 km 2, and estimates by Brownian bridge and minimum convex polygon were also provided. The anteater used shrub savanna, open savanna, and water habitats more than expected. Monitoring ended just after 10 days when the female giant anteater's GPS was found on an illegal trail.